A study of the quantity of materials from computer scraps recycling process - Kamnerdwam, Apichon; Rattanamanee, Wanida; Sinthavalai, Runchana; Suntiamorntut, Wannarat (Asia-Pacific Journal of Science and Technology, 2017)
Nowadays, the quantity of computer scraps both desktop and notebook computer in Thailand has increased continuously. In addition, Thailand still lack of the appropriate and efficient system for management. Hence, this research aims to investigate and estimate the quantity of recycled materials from computer scraps which reflect to the quantity of material can be reused. This research consists of the estimation of computer scraps, presenting of technologies and recycling processes, and the estimation of recycled materials. The results showed that the estimation of quantity of computer scraps, desktop computer and notebook computer scraps in 2015 are about 4,222,291 units or 57.88% and 3,072,827 units or 42.12% respectively. For the application of the three levels of recycling technology with an efficiently recycling process can provide the quantity of materials in 2015, such as plastics, iron, aluminum, copper, lead, tin, silver and gold were equal 6,027,634 kg, 20,953,216 kg, 14,258,370 kg, 7,890,813 kg, 361,943 kg, 818,017 kg, 25,484 kg, and 2,934 kg respectively. As can be seen, the recycling process can provide valuable parts. Finally, the appropriate way for supporting the future management of computer scraps is to develop a system for taking computer scraps back and propose to the recycling process.